Introduction to the establishment of tribunal in Malaysia - Amin, Naemah (2013)
A tribunal system has been recognised as part of the administration of justice in every democratic country including Malaysia. Tribunal emerges as part of the development of socio-economic legislation such as Acts relating to employment, consumer protection and income tax. The paper provides an overview of the establishment and development of tribunal system in Malaysia, it stucture and basic features. It also highlights the differences between the Tribunals and ordinary court system as well as advantages and disadvantages of the tribunal system. The main concern of current system is that there is no discernible pattern or structural design in setting up Tribunal in Malaysia. Thus there is a need for a proper structure, procedure and monitoring of Tribunals to be more effective and systematic.